The Islamic Characters in The Novel Markesot Bertutur by Emha Ainun Najib - Evi Chamalah; Agus Nuryatin; Suminto A. Sayuti; Ida Zulaeha (Ar-Raniry: International Journal of Islamic Studies, 2018)
Character in literature plays an important role in constructing human identity. One of the characters in the literature is the Islamic character values. The Islamic character consists of four aspects namely faith (aqidah), worship (ibadah), muamalah, and morals. The novel Markesot Bertutur is one of the novels that has Islamic character values. In this novel, there are 21 values of faith, 13 values of morals, and 188 values of worship.